Blood screening for human immunodeficiency virus: a new algorithm to reduce the false‐positive results. Issue 4 (2nd May 2013) - Zhang, R.; Sun, Y.; Wang, L.; Zhang, K.; Xie, J.; Li, J.
SUMMARY: Objectives: The objectives to this study were to evaluate the performance of an anti‐human immunodeficiency virus (HIV) blood screening test and propose a new screening algorithm for blood banks routinely using nucleic acid amplification testing (NAT) to reduce false‐positive results. Background: Most anti‐HIV enzyme‐linked immunosorbent assay (ELISA) results are false‐positive because of the low prevalence of HIV infection and high sensitivity of the ELISAs. Methods/Materials: A total of 281 588 voluntary donations were collected and sera reactive on one or both anti‐HIV ELISAs were confirmed by Western blot (WB) testing. All samples with nonreactive results for the two ELISAs underwent NAT. A confirmed HIV‐1‐positive result was defined by a reactive result on NAT or WB testing. Correlations between signal‐to‐cutoff ratios and the confirmed HIV‐1 infection rate were analysed for each enzyme immunoassay and two‐enzyme immunoassay combination. The positive predictive values (PPVs) of the current and proposed algorithms were calculated. Results: Seventy‐nine donations (13·9%) were positive on WB analysis and one donation negative for anti‐HIV antibody was reactive on NAT and confirmed to be a window period donation on additional follow‐up testing. The PPV of the 567 donations reactive on one or two ELISAs was 13·9%. However, using the new screening algorithm, 457 donations underwent NAT immediately instead of WB testing. Only 110 donations were tested with WB and the PPV was 71·8%. Conclusion: Screening for HIV is sensitive, specific and time saving for donors with this algorithm, which is suitable for HIV screening in low prevalence settings.